Development of phytonutrient enriched avocado milkshake powder and its quality evaluation - Pandey, Shreya; Kumari, Aparna; Varghese, K Shiby; Chauhan, Anil Kumar; Singh, Meenakshi (Indian Journal of Dairy Science, 2020)
Consumers are progressively searching out food with good taste that can be instantly prepared, easily consumable, and wholesome. Avocado is nutritious fruit but its preservation is a challenge for food researchers. A new freeze-dried milkshake powder is developed by using avocado. This product provides healthful mixture of dairy and fruit components with high nutritional and longer shelf-life. Butter fruit milkshake powder (BFMS) formulation was prepared by mixing avocado pulp, pasteurized milk, maltodextrin, and sugar in the ratio of 84%, 28%, 10%, and 6% respectively. BFMS were analyzed for proximate composition, physiochemical, and flow properties. Results showed that the inclusion of milk and maltodextrin increase protein, fat, ash content, and preserve phenolic, flavonoid, and Ã¢-carotene content of the avocado pulp. The freeze-dried BFMS powder has light color, lower water activity, and instant water-solubility (30 sec). For powder rheology, BFMS provided better flowability and decreased compressibility. BFMS is beneficial for all age groups, especially for armed forces because of instant solubility, lightweight texture, and is highly nutritious.